(untitled) (Acta Scientiarum. Agronomy, 2008)
One of the greatest problems in the elaboration of forestation programs using native species is the lack of knowledge about seedling production. This study aimed to evaluate the growth of Bauhinia forficate seedlings submitted to phosphorus levels. Eleven-day-old seedlings were transplanted to small tubettes (110 cm3) with pinus bark and vermiculite substratum base. The experiment was conducted in an entirely randomized delineation, with six P treatments: T0-control (substratum without P addition), T1-50, T2-100, T3-150, T4-200 and T5-250 mg dm-3, with five replications and 20 seedlings per replication. After 60 days, the seedlings presented a 98.2% survival rate and good root formation. The height varied in function of P levels, with maximum production up to the P dose of 250 mg dm-3; 60 days after the transplant, similar behavior for leaf area and dry matter production was observed. Furthermore, the P incorporation increased the phosphorus (P), potassium (K) and nitrogen (N) accumulation in vegetable tissues. Seedling growth was positively influenced by P levels, and the maximum growth occurred up to the P dose of 250 mg dm-3,/sup>. In conclusion, this characteristic showed that the species requires high levels of P during initial growth, under the tubette system.